Business continuity planning : a case study of NTUC income insurance cooperative limited. - Ho, Lee Wen. (2008)
This project outlines the key content of BCP and the issues to be addressed in planning for one to ensure it meets real business recovery needs. In addition, we also did a case study on NTUC Income Cooperative Limited to gain an insight of the factors influencing successful BCP in local context.